Pastor Seller, E. (Ed.) (2017). Sistemas y políticas de bienestar, una perspectiva internacional. Madrid: Dykinson. - Martínez Gallardo, Blas José (AZARBE, Revista Internacional de Trabajo Social y Bienestar, 2017)
Pastor Seller, E. (Ed.) (2017). Sistemas y políticas de bienestar, una perspectiva internacional. Madrid: Dykinson.